Serological investigation of bovine brucellosis in three cattle production systems in Yewa Division, South-Western Nigeria (2013)
Limited data are available on the risk factors responsible for the occurrence of brucellosis amongst different cattle production systems in Nigeria despite its significant impact on livestock production. Consequently, a cross-sectional study was conducted to determine the prevalence of bovine brucellosis in three cattle production systems in Yewa Division of Ogun State, south-western Nigeria. A total of 279 blood samples (sedentary = 88; transhumance = 64; trade = 127) were examined for antibodies to Brucella sp. using the Rose Bengal test (RBT) and competitive enzyme-linked immunosorbent assay (cELISA). Overall, 24 (8.6%) and 16 (5.7%) of the animals tested seropositive for Brucella using RBT and cELISA, respectively. The herd seroprevalences based on RBT and cELISA were 31.6% and 15.8%, respectively. The results using cELISA reveal higher seroprevalence in the trade cattle (7.9%; confidence intervals [CI] = 3.2% – 12.6%) and those in a sedentary system (5.7%; CI = 0.9% – 10.5%) than in cattle kept under a transhumant management system (1.6%; CI = 1.5% – 4.7%). Age (> 3 years; p = 0.043) and breed (Djali; p = 0.038) were statistically significant for seropositivity to brucellosis based on cELISA, but sex (female, p = 0.234), production system (trade and sedentary; p = 0.208) or herd size (> 120; p = 0.359) was not. Since breeding stock is mostly sourced from trade and sedentary cattle, it is important that routine serological screening should be conducted before introducing any animal into an existing herd.